K-Domain Technology: Constitutive Expression of a Blueberry Keratin-Like Domain Mimics Expression of Multiple MADS-Box Genes in Enhancing Maize Grain Yield - Song, Guo-qing; Han, Xue (Frontiers in Plant Science, 2021)
MADS-box genes are considered as the foundation of all agronomic traits because they play essential roles in almost every aspect of plant reproductive development. Keratin-like (K) domain is a conserved protein domain of tens of MIKC-type MADS-box genes in plants. K-domain technology constitutively expresses a K-domain to mimic the expression of other MADS-box genes simultaneously and thus to generate new opportunities for yield enhancement. In this study, we evaluated utilizing the K-domain technology to increase maize yield. The K-domain of a blueberry’s SUPPRESSOR of CONSTITUTIVE EXPRESSION OF CONSTANS 1 (VcSOC1K) has similarities to five MADS-box genes in maize. Transgenic maize plants expressing the VcSOC1K showed 13% - 100% of more grain per plant than the nontransgenic plants in all five experiments conducted under different experimental conditions. Transcriptome comparisons revealed 982 differentially expressed genes (DEGs) in the leaves from 83-day old plants, supporting that the K-domain technology were powerful and multiple functional. The results demonstrated that constitutive expression of the VcSOC1K was very effective to enhance maize grain production. With the potential of mimicking multiple MADS-box genes, the K-domain technology opens a new approach to increase crop yield.